Unusual O‐Bridged Symmetric Quinoline‐Based Ligand for the Formation of Luminescent Mono‐Aqua Lanthanide Complexes. Issue 21 (24th October 2016) - Hammoud, Hassan; de Bettencourt‐Dias, Ana; Schmitt, Martine; Monteiro, Jorge H. S. K.; Rossini, Jeffrey S.; Lecointre, Alexandre; Gallet, Sébastien; Bourguignon, Jean‐Jacques; Mameri, Samir
Abstract: A novel ligand based on a O‐bridged symmetrical bis‐quinoline containing carboxylate moieties has been synthesized and its coordination and sensitization ability for lanthanide ions has been studied in aqueous solution. The efficient 7‐step methodology developed starts from commercial 8‐methylquinoline. This new heterocycle, which was characterized in the solid state and in solution, displays interesting spectroscopic properties in water with an absorption below 350 nm. The coordination behaviour of this ligand with trivalent lanthanide cations (Ln=Eu, Tb and Gd) in solution leads to the formation of stable complexes with [LnL ] stoichiometry, which were isolated from neutral water solutions containing equimolar amounts of cations and ligand. The photophysical properties of the mononuclear complexes of Eu and Tb were studied in aqueous solution by absorption, excitation and emission spectroscopy. Comparison of the luminescence lifetimes of the Eu and Tb complexes in H2 O and D2 O reveals the presence of 1 water molecule in the first coordination sphere of the metal ions. The sensitized emission efficiency of the Eu complex in water is good, as demonstrated by a quantum yield of 9.5(7)%. The analogous Tb(III) complex displays an emission efficiency of 2.0(1)%. This low value is indicative of incomplete energy transfer, which is supported by a decay lifetime that can be fit to a double exponential, due to residual ligand emission. Abstract : The synthesis of a novel sophisticated heterocyclic molecule is reported, which proved to be suitable for the coordination and sensitization of light‐emitting Eu(III) and Tb(III) lanthanide cations. The mononuclear complexes show 1 water molecule in the first coordination sphere of the metal ions, which also display interesting luminescence quantum yields and lifetimes in water solution, e. g. 9.5 % and τ=523μs, for Eu(III).